The impact of leadership on organizational ambidexterity and employee psychological safety in the global acquisitions of emerging market multinationals. Issue 20 (12th November 2016) - Rao-Nicholson, Rekha; Khan, Zaheer; Akhtar, Pervaiz; Merchant, Hemant
Abstract : This paper examines the impact of leadership on organizational ambidexterity and employee psychological safety (EPS) based on a sample of 105 global acquisitions of emerging market multinationals. The findings suggest that, compared to the transactional and laissez-faire ones, the charismatic leadership style is more significantly related to organizational ambidexterity and EPS. The results also suggest that transactional leadership is more positively related to ambidexterity and EPS than laissez-faire leadership. In addition, organizational ambidexterity is directly and positively associated with EPS. The implications of these results for both research and practice are discussed in the paper.